2020
DOI: 10.1007/s12015-020-10050-5
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-17 ~ 92 Family as a Key Regulator of Neurogenesis and Potential Regenerative Therapeutics of Neurological Disorders

Abstract: miR-17 ~ 92, an miRNA family containing three paralogous polycistronic clusters, was initially considered as an oncogene and was later demonstrated to trigger various physiological and pathological processes. Emerging evidence has implicated miR-17 ~ 92 family as a master regulator of neurogenesis. Through targeting numerous genes that affect cell cycle arrest, stemness deprivation, and lineage commitment, miR-17 ~ 92 family controls the proliferation and neuronal differentiation of neural stem/progenitor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 81 publications
1
7
0
1
Order By: Relevance
“…Increased levels of miRNA-23a-3p inhibit the CXC chemokine receptor 4 (CXCR4) in spinal glial cells, which is directly responsible for neuropathic pain. miR-17-92 cluster (containing: miR-17, miR-18a, miR-19a, miR-20a, miR-19b-1, and miR-92a-1) is an important factor regulating neurogenesis, neuronal differentiation and showing great potential in the treatment of neurodegenerative diseases [38,39]. In our study, we observed an increase in the expression of most of the miRNAs in this family.…”
Section: Discussionsupporting
confidence: 58%
“…Increased levels of miRNA-23a-3p inhibit the CXC chemokine receptor 4 (CXCR4) in spinal glial cells, which is directly responsible for neuropathic pain. miR-17-92 cluster (containing: miR-17, miR-18a, miR-19a, miR-20a, miR-19b-1, and miR-92a-1) is an important factor regulating neurogenesis, neuronal differentiation and showing great potential in the treatment of neurodegenerative diseases [38,39]. In our study, we observed an increase in the expression of most of the miRNAs in this family.…”
Section: Discussionsupporting
confidence: 58%
“…Secondly, mir-17 and 20a expressions were higher in overall AR-negative and QNBC samples. MYC positively regulates mir-17 and 20a (38) (39). MYC expression was higher in QNBCs, and FOXA1 was lower in QNBCs.…”
Section: Discussionmentioning
confidence: 92%
“…al. these 3 miRNAs share the same seed sequence and thus are thus predisposed to clustering closely [37]. The role of miR-17/92 in tumorigenesis in humans and consequent effect on aging due their dysregulation have been demonstrated already [38,39].…”
Section: Cluster 11mentioning
confidence: 99%